Flow states and heat transport in Rayleigh–Bénard convection with different sidewall boundary conditions. (10th April 2022) - Reiter, Philipp; Zhang, Xuan; Shishkina, Olga
Abstract: Abstract : This work addresses the effects of different thermal sidewall boundary conditions on the formation of flow states and heat transport in two- and three-dimensional Rayleigh–Bénard convection (RBC) by means of direct numerical simulations and steady-state analysis for Rayleigh numbers ${Ra}$ up to $4× 10^{10}$ and Prandtl numbers ${Pr}=0.1, 1$ and $10$ . We show that a linear temperature profile imposed at the conductive sidewall leads to a premature collapse of the single-roll state, whereas a sidewall maintained at a constant temperature enhances its stability. The collapse is caused by accelerated growth of the corner rolls with two distinct growth rate regimes determined by diffusion or convection for small or large ${Ra}$, respectively. Above the collapse of the single-roll state, we find the emergence of a double-roll state in two-dimensional RBC and a double-toroidal state in three-dimensional cylindrical RBC. These states are most prominent in RBC with conductive sidewalls. The different states are reflected in the global heat transport, so that the different thermal conditions at the sidewall lead to significant differences in the Nusselt number for small to moderate ${Ra}$ . However, for larger ${Ra}$, the heat transport and flow dynamics become increasingly alike for different sidewalls and are almost indistinguishable for ${Ra}>10^{9}$ . This suggests that the influence of imperfectly insulated sidewalls in RBC experiments is insignificant at very high ${Ra}$ – provided that the mean sidewall temperature is controlled.